Physicochemical Properties and Consumer Acceptance of Hamburgers Processed with Chicken Meat Affected by Wooden Breast Myopathy - Oliveira, Rodrigo Fortunato de [UNESP] (2020)
Simple Summary The study of meat quality of modern birds and their respective myopathies is important to understand the influence of myopathy on the meat quality of these birds. The constant genetic evolution that birds have suffered and still suffer in the present is the most plausible cause of the onset of this myopathy. The processing of by-products, such as hamburgers, enters as an alternative to avoid losses that this myopathy generates in the poultry industry, with discards of chickens affected by the different degrees of myopathy in wooden breast. Considering the increased incidence of wooden breast myopathy in broilers, the intake involves no threat to human health, indefinite etiology consumer rejection by appearance in such breasts, and the lack of studies on the industrial use of wooden breast. The objective of this study was evaluating the quality of hamburgers made with chicken meat affected by wooden breast. Breast samples from broilers slaughtered at 48-days-old were used. Normal (absence of myopathy), moderate degree (hardness only in one region of the breast) and severe degree (hardness over the entire length of the breast) samples were processed for the manufacture of hamburgers whose quality analyses (color, pH, cooking weight loss, shrinkage percentage, tenderness, storage weight loss, water activity, lipid oxidation, chemical composition and consumer test) were performed on non-stored samples (Day 0), and after storing at 30, 60, 90 and 120 days at -20 degrees C. There was a reduction (p < 0.05) in tenderness in samples of moderate-grade hamburgers (from 161.45 N to 289.40 N) after 120 days of storage. Hamburgers produced with chicken breast samples affected by wooden breast myopathy presented higher (p < 0.0001) fat concentration (5.32 g/100 g and 5.26 g/100 g, respectively, for the moderate and severe degree) than hamburgers made of normal samples (4.45 g/100 g). Lipid oxidation values increased, which exceeded the limit of rancidity detection, independent of myopathy. The consumers equally appreciated the aroma, flavor, and texture, and rated their overall acceptance as similar regardless of the quality of chicken meat. Chicken breast hamburgers with wooden breast myopathy is a viable alternative for the poultry industry.